Development of real-time PCR and droplet digital PCR based marker for the detection of Tilletia caries inciting common bunt of wheat - Ren, Zhaoyu; Chen, Rongzhen; Muhae-Ud-Din, Ghulam; Fang, Mingke; Li, Tianya; Yang, Yazheng; Chen, Wanquan; Gao, Li (Frontiers in Plant Science, 2022)
This is the first study reporting droplet digital PCR and quantitative real time PCR for detection of Tilletia caries (syn. T. tritici), which causes common bunt of wheat and leads to yield losses of 80% in many wheat growing areas worldwide. To establish an accurate, rapid and quantifiable detection method, we tested 100 inter simple sequence repeats (ISSR) primers and obtained a species-specific fragment (515 bp) generated by ISSR 827. Then, a specific 266 bp band for the sequence characterized amplified region (SCAR) marker was produced from T. caries. The detection limit reached 50 pg/μL. Based on the SCAR marker, we further de-veloped a higher sensitivity of quantitative real time-polymerase chain reaction (qRT-PCR) with a detection limit of 2.4 fg/μL, and droplet digital PCR (ddPCR) with a detection limit of 0.24 fg/μL. Both methods greatly improved the detection sensitivity of T. caries, which will be contribute a lot for quickly and accu-rately detection of T. caries, which causes wheat common bunt.